The Effectiveness of Post-Pandemic Hybrid PAI Learning (Blended Learning) on the Formation of Religious Character in State Madrasah Ibtidaiyah 1 Yogyakarta Students - Tsaaniyatush Shoolihah Fauzan (Aslama: Journal of Islamic Studies, 2025)
This study examines the effectiveness of hybrid learning (blended learning) in Islamic Religious Education (PAI) post-pandemic in forming the religious character of Madrasah Ibtidaiyah students. The COVID-19 pandemic transformed the learning paradigm from conventional to digital, and post-pandemic, a hybrid model emerged combining face-to-face learning with online learning. This research employs a qualitative approach with a case study method at MI Negeri 1 Yogyakarta. Data were collected through observation, in-depth interviews with PAI teachers, the madrasah principal, students, and parents, as well as documentation. The results show that hybrid PAI learning is effective in forming students' religious character, reflected in increased understanding of religious values, daily worship practices, and noble morals. Supporting factors include digital infrastructure availability, teacher competence in learning technology, and parental support. The challenges faced include technological access gaps, lack of direct social interaction, and supervision of students' worship practices. This study recommends developing a more structured hybrid PAI curriculum, continuous teacher training, and strengthening collaboration between madrasah and families.